Experimental Study and Modelling of Coffee Bean Roasting in Rotary Drum Roaster on Maillard Reaction Products - Michelle Haury (13014081), Ian Otard Kognac (13014111) , Gabriella
Roasting leads to numerous physical and chemical transformations that create the taste, aroma, and color of roasted coffee. Out of the many chemical components formed during coffee roasting, melanoidin is a major contributor to coffee color. Melanoidin is also a chemical component with many health benefits, including its antioxidant property. The quality of coffee is highly affected by roasting process conditions, namely roasting temperature and drum rotation speed. This research is conducted to study the effects of roasting conditions in a rotary drum roaster on color, antioxidant activity, and melanoidin content in brewed coffee. A heat and mass transfer model of coffee roasting using hot air has been developed and validated with experiments to show how the process parameters influence product properties. From the experiment results, a statistical model was also built based on regression for the purpose of predicting how roasting conditions may affect coffee quality variables. Arabica coffee beans were roasted at 200, 230, and 260 Ã‚Â°C with drum rotation speed at 74 rpm, 83 rpm, and 0 rpm (without rotation). Melanoidin isolation was done using ultrafiltration, followed by characterization using Kmix value. Antioxidant activity in coffee was measured by its radical scavenging activity value when free radical DPPH is added to coffee. Color measurement was performed using colorimeter to obtain L*, a*, and b* parameters. From obtained data, deterministic and statistical model is created to predict coffee quality parameters based on operating condition input. Experimental results show that increment in roasting temperature and drum rotation speed caused significant increase in coffee melanoidin content, while antioxidant activity decreased. L*, a*, and b* parameters could be used to show the degree of color formation reactions, however it can not solely be used to determine degree of roast as coffee quality parameters are highly affected by roasting conditions. Developed model is able to give trend on moisture content and temperature change in roasting, although error between model and experimental data is still present.